Radiation Dose Measurement Technique of the X-Ray Source in the Process of Stabilization; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Krasnykh A. A. Angelina Aleksandrovna; Wagner A. R. Aleksandr Rudolfovich (2015, 2015)
Title screen